Exploring the use of 5 different Yo-Yo tests in evaluating VO2max and fitness profile in team sports: a systematic review and meta-analysis - Tan, Z.; Castagna, C.; Krustrup, P.; Wong, D. P.; Póvoas, S.; Boullosa, D.; Xu, K.; Cuk, I. (Scandinavian Journal of Medicine & Science in Sports, 2025)
This review aims to examine the relationship between five different Yo-Yo tests and VO2max as well as performance in various fitness tests, to provide practical guidance for fitness assessment. Thirty-three studies (n = 1362) were analyzed to qualitatively score correlation magnitude (r-values) between five different Yo-Yo tests with VO2max. The association between Yo-Yo tests and physical fitness tests were examined including 36 studies (n = 1262 participants). Large correlations were found between VO2max and Yo-Yo Intermittent Endurance level 1 (r = 0.67), and level 2 (r = 0.67), Yo-Yo Intermittent Recovery level 1 (r = 0.65), and level 2 (r = 0.55). Yo-Yo tests showed moderate correlations with the jump tests (r = 0.40). Large associations were reported between Yo-Yo tests performance and treadmill endurance test (r = 0.59) and the field-based endurance tests (r = 0.66), respectively. These findings confirm Yo-Yo tests as reliable and valid tests for estimating VO2max and endurance performance in team sports, supporting their integration in structured testing batteries. Coaches should supplement Yo-Yo tests with specific strength and sprint assessments for a comprehensive fitness evaluation of the team sport athletes.